Challenge-hindrance appraisal job and work-life balance among teachers in Sabah - Pan, Lee Ching; Chua, Bee Seok (Secholian Publication PLT, 2018)
Work-life balance is a prerequisite, in the choice of contemporary work styles, but allegedly has deteriorated in the teaching profession. Affected work-life quality causes serious impacts including work-life conflict, decreased job ability and affects an individual’s psychological state. This distress wave affects on a global scale, due to extreme workloads which cause high job stress that eventually affect quality of life. In the Malaysian context, job stress is currently at a medium level, but workloads are expected to increase, hence, work-life balance is potentially at risk. Investigations into work-life balance among teachers in Sabah is scarce. In addition, studies have not adequately examined the issue with positive integration. Balancing is about strengthening the known gains, and overcoming the identified strains. Thus, present conceptual paper discussed about the relationship of workload, eustress and distress towards work-life balance. Ultimately, a conceptual framework is developed based on the reviewed literature.